2015
DOI: 10.1177/1358863x14565372
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the relationship between ankle–brachial and toe–brachial indices and infragenicular arterial patency in critical limb ischemia

Abstract: The relationship between ankle-brachial index (ABI) remains uncertain relative to clinical and angiographic features of critical limb ischemia (CLI). From July 2011 to February 2013, 89 consecutive patients with CLI had non-invasive testing for indications of rest pain (n=23, 26%), as well as minor (n=29, 33%) and major (n=37, 42%) ischemic tissue loss. All patients subsequently underwent ABI testing and lower extremity angiography with visualization of the infragenicular arteries. Toe-brachial index (TBI) tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 16 publications
4
67
0
1
Order By: Relevance
“…Although reasons for this are unclear, rest pain is often caused by multilevel obstruction to arterial flow rather than discrete blockage (as is more commonly observed in patients with wounds) 19, 20. Furthermore, the occurrence of wound healing suggests response to therapy and adequate tissue perfusion, which may infer better outcomes than patients with persistent rest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although reasons for this are unclear, rest pain is often caused by multilevel obstruction to arterial flow rather than discrete blockage (as is more commonly observed in patients with wounds) 19, 20. Furthermore, the occurrence of wound healing suggests response to therapy and adequate tissue perfusion, which may infer better outcomes than patients with persistent rest pain.…”
Section: Discussionmentioning
confidence: 99%
“…A falsely elevated ABI may result from autonomic neuropathy and medial arterial calcinosis. Combination testing thus helps to improve diagnostic accuracy in this subgroup . Nonetheless, PAD is a less likely diagnosis in the presence of ABI 0.9 to 1.3, TBI ≥ 0.75 and triphasic pedal Doppler waveforms…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, the recommended changes in ankle pressure, ABI, toe pressure, and TBI do not reflect an association with major adverse limb events (MALE) . Recent studies , including an analysis from the core laboratory‐adjudicated multicenter IN.PACT DEEP (randomized amphirion DEEP DEB vs standard PTA for the treatment of below the knee critical limb ischemia) trial, had showed that baseline TBI and toe pressure were markedly superior to ABI and ankle pressure in uncovering the presence of CLI by accurately reflecting the degree of hemodynamic impairment . Given the clinical and outcome differences among patients with claudication and CLI, especially in those with severe infragenicular disease, we sought to describe observed changes in ankle pressure, ABI, toe pressure, and TBI following revascularization and their association with MALE in this multicenter international core lab‐adjudicated clinical trial.…”
Section: Introductionmentioning
confidence: 99%